Effects of a 5-Day Back Squat Overreaching Protocol on Strength Performance, Perceived Recovery and Wellness Responses: A Pilot Trial - Lee Bell; Alan Ruddock; Jordan Boriel; Tom Maden-Wilkinson; Steve W. Thompson; Kieran J. Wright; Kieran Burke; David Rogerson (Journal of Functional Morphology and Kinesiology, 2025)
Background: The aim of this study was to characterise the performance, perceptual, and wellness responses to a barbell back squat overreaching training protocol. Methods: Eight trained male participants (age = 24.6 ± 2.8 years; relative to body mass back squat one repetition maximum (1-RM) = 1.9 ± 0.4; training experience = 7.0 ± 3.2 years) participated in a 5-day squat OR protocol (SqOR), followed by a 14-day taper. SqOR consisted of five sets of barbell back squats using 80% of daily adjusted 1-RM. A 40% velocity loss threshold was used to determine the set end point. For performance, isometric mid-thigh pull (IMTP) peak force (PF), and countermovement jump (CMJ) PF and jump height; for perceptual, perceived recovery scale (PRS); and for wellness, Hooper Wellness Index (HWI), were recorded at baseline, each day of SqOR, and at select intervals during the taper (POST 1 d, 2 d, 7 d, and 14 d). Follow-up back squat 1-RM testing was conducted at POST 7 d and POST 14 d to determine strength-performance changes relative to baseline. Results: Back squat 1-RM increased by 4.8% at POST 7 d and 5.2% at POST 14 d. IMTP PF increased by 10.3% at POST 7 d and 11.4% at POST 14 d relative to the baseline. CMJ PF and jump height decreased during SqOR but returned to baseline by POST 7 d. PRS and HWI worsened during SqOR, with the greatest impairment occurring on day 3 (PRS = −41.5%; HWI = 34.4%), and did not return to baseline until POST 14 d and POST 2 d, respectively. Conclusions: These findings demonstrate that a short-term period of planned OR improves muscular strength performance, but the duration of the taper influences when peak strength improvements are observed.